2019
DOI: 10.1096/fj.201900095r
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with dietary ω‐3 mitigates immobilization‐induced reductions in skeletal muscle mitochondrial respiration in young women

Abstract: Omega‐3 (ω‐3) supplementation attenuates immobilization‐induced atrophy; however, the underlying mechanisms remain unclear. Since mitochondrial dysfunction and oxidative stress have been implicated in muscle atrophy, we examined whether ω‐3 supplementation could mitigate disuse‐mediated mitochondrial dysfunction. Healthy young women (age = 22 ± 3 yr) randomly received control (n = 9) or ω‐3 supplementation (n = 11; 3 g eicosapentaenoic acid, 2 g docosahexaenoic acid) for 4 wk prior to and throughout 2 wk of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
3
48
1
1
Order By: Relevance
“…), and our recent work highlighting that leg immobilization rapidly impairs mitochondrial respiratory capacity in as little as 3 days (Miotto et al . ). In the present study, the reduction in respiratory capacity coincided with a reduction in OXPHOS proteins.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…), and our recent work highlighting that leg immobilization rapidly impairs mitochondrial respiratory capacity in as little as 3 days (Miotto et al . ). In the present study, the reduction in respiratory capacity coincided with a reduction in OXPHOS proteins.…”
Section: Discussionmentioning
confidence: 97%
“…; Miotto et al . ). While these data suggest temporally oxidative phosphorylation is impaired, inducing mitophagy, in contrast, a recent report has also shown that 4 days of strict bed rest reduced mitochondrial content in the absence of a reduction in respiratory capacity (Larsen et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although, when mitochondrial respiration was normalised to CS activity these decreases were no longer statistically different [56]. Despite this, single leg immobilization decreases respiration before any changes in the expression of components of the respiratory chain [104]. This suggests that changes in mitochondrial respiratory function may occur prior to changes in content, which may take a longer time to occur.…”
Section: Physical Activitymentioning
confidence: 89%